Representation of different exact numbers of prey by a spider-eating predator. Issue 3 (21st April 2017) - Cross, Fiona R.; Jackson, Robert R.
Abstract : Our objective was to use expectancy-violation methods for determining whether Portia africana, a salticid spider that specializes in eating other spiders, is proficient at representing exact numbers of prey. In our experiments, we relied on this predator's known capacity to gain access to prey by following pre-planned detours. After Portia first viewed a scene consisting of a particular number of prey items, it could then take a detour during which the scene went out of view. Upon reaching a tower at the end of the detour, Portia could again view a scene, but now the number of prey items might be different. We found that, compared with control trials in which the number was the same as before, Portia 's behaviour was significantly different in most instances when we made the following changes in number: 1 versus 2, 1 versus 3, 1 versus 4, 2 versus 3, 2 versus 4 or 2 versus 6. These effects were independent of whether the larger number was seen first or second. No significant effects were evident when the number of prey changed between 3 versus 4 or 3 versus 6. When we changed prey size and arrangement while keeping prey number constant, no significant effects were detected. Our findings suggest that Portia represents 1 and 2 as discrete number categories, but categorizes 3 or more as a single category that we call 'many'.